Gastroesophageal Intussusception in Canine - Waterloo, Mateus de Melo Lima; Gonçalves, Saulo Romero Felix; Araújo, Ebla Lorena Sales de; Ferreira, Ana Paula dos Santos; Albuquerque, Pedro Paulo Feitosa de; Oliveira, Andrea Alice da Fonseca; Pereira, Márcia de Figueiredo (Acta Scientiae Veterinariae, 2021)
Background: Gastroesophageal intussusception is characterized by the invagination of the stomach into the esophagus, with or without the involvementof adjacent organs such as the spleen, pancreas, and omentum. In dogs, this condition has no breed or sex predisposition. As it is an infrequent disease in routine veterinary medical practice, this study reports a case of gastroesophageal intussusception in a dog necropsied at the Veterinary Hospital of the Federal Rural University of Pernambuco (HOVET - UFRPE), Recife, Brazil. Case: The body of a 12-year-old black mixed breed male dog was sent to the Pathology Department (Necropsy Sector of the Federal Rural University of Pernambuco - UFRPE) for a necropsy. The animal had a previous 4-year history of recurrent emesis and limb weakness, primarily in the anterior limbs, that worsened in the previous months and progressed to death. No previous treatments were reported by the owner. On external examination, the animal had a low body score (cachectic), forelimb joints with great flexibility, congested oral and ocular mucous membranes, enophthalmos, and increased volume in the perianal region. At the opening of the thoracic cavity, the final third of the esophagus was dilated and gastroesophageal intussusception, edema, and pulmonary congestion were noted. In the abdominal cavity, there was hepatic and renal congestion and large intestine and rectal ampoule dilation, with a large amount of solid and retained feces (fecaloma), perianal hernia, and testicular neoformation. These findings were consistent with those observed in death caused by cardiorespiratory failure secondary to gastroesophageal intussusception. Discussion: The pathophysiology of gastroesophageal intussusception is still not elucidated and is probably multifactorial. This condition causes reverse gastric peristalsis associated with a sudden and sustained increase in abdominal pressure. Some probable predisposing factors for this pathological condition are esophageal motility disorders, lower esophageal sphincter dysfunction, and hiatal enlargement. In dogs, gastroesophageal intussusception is associated with increased intra-abdominal pressure owing to emesis or blunt trauma, negative intrathoracic pressure caused by respiratory, and previous esophageal diseases, especially megaesophagus. Partial or total obstruction caused by intussusception leads to circulatory disorders in the organs, especially decreased venous return. Persistence of this condition can lead to gastric necrosis and rupture followed by endotoxic (or septic) shock and release of inflammatory mediators that can cause cardiovascular and respiratory dysfunction and rapid death. Impaired circulation is macroscopically evident in several organs, characterized by mucosal, lung, liver, and kidney congestion, in addition to cardiac dilation and mitral valve endocardiosis. The occurrence of stomach invagination into the esophagus dilated in the final portion is characteristic of gastroesophageal intussusception. Moreover, death owing to cardiorespiratory failure is related to cardiac (dilatation and endocardiosis) and pulmonary (edema and congestion) involvement secondary to gastroesophageal intussusception. Since thispotentially fatal condition has a low incidence in small animals and often goes unnoticed by professionals, early and correct diagnosis along with surgical treatment are essential for a good prognosis and favorable progression.